Laminins in Cellular Differentiation. Issue 12 (December 2019) - Yap, Lynn; Tay, Hwee Goon; Nguyen, Mien T.X.; Tjin, Monica S.; Tryggvason, Karl
Abstract : Basement membrane laminins (LNs) have been shown to modulate cellular phenotypes and differentiation both in vitro and during organogenesis in vivo . At least 16 laminin isoforms are present in mammals, and most are available as recombinant proteins. Ubiquitous LN511 and LN521 promote the clonal derivation and expansion of pluripotent embryonic stem cells (ESCs), and, together with other highly cell type-specific laminins, they can support the differentiation of stem cells into, for example, cardiac muscle fibers, retinal pigmented epithelial (RPE) cells and photoreceptors, dopamine (DA) neurons, and skin keratinocytes. The laminin-supported differentiation methods are highly reproducible and can be made chemically defined and fully xeno-free – a prerequisite for preparing therapeutic stem cell-derived cells. In this review we describe recent work on the use of laminin-based cell culture matrices in stem cell differentiation. Highlights: Components of the extracellular matrix (ECM) have been implicated in stem cell differentiation, in stem cell niches, and during morphogenesis. The laminin protein family of basement membranes (BMs) contains at least 16 different isoforms, most of which are currently available in pure form as recombinant human proteins. Various recombinant human laminins have been studied for their effects on cellular differentiation and they have been shown to enable the development of fully human, chemically defined and highly reproducible methods for differentiation to a variety of cell types. Laminin-based cell culture and differentiation methods are likely to find extensive use in the development of new human embryonic stem cell lines and in generating therapeutic human stem cell-derived cell types for regenerative medicine.